(untitled) (Texas Journal of Philology, Culture and History, 2024)
Chronic obstructive pulmonary disease (COPD) is a serious health problem today. Every year there is an increase in the number of cases of COPD around the world, which is accompanied by a deterioration in the quality of life of patients, temporary loss of ability to work, and even death. Deficiencies of macro- and microelements are currently recognized by world medicine as a global problem. These conditions have a significant impact on the body, presenting an urgent need for the development of effective health strategies to address them. According to available data, nutritional deficiencies are quite common in patients with COPD. Numerous studies highlight the impact of micronutrient deficiencies on disease progression. Currently, the connection between bronchopulmonary diseases and low levels of vitamin D and magnesium in the body of patients is being actively studied. Insufficient outdoor activity, infrequent exposure to sunlight, poor diet, alcoholism, smoking, decreased ability of the skin to synthesize vitamin D in smokers, general exhaustion of the body, and the use of certain antibiotics can be the causes of low levels of vitamin D and magnesium. Many studies indicate that deficiencies of these elements may be associated with decreased lung function and increased exacerbations in COPD, which contributes to disease progression. Deficiency conditions, which often remain undiagnosed, can negatively affect the prognosis of the disease. This study identifies the incidence of low blood levels of vitamin D and magnesium and demonstrates the relationship between low levels of these elements and the severity of COPD.